2016
DOI: 10.1038/nmat4570
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable scaffold with built-in vasculature for organ-on-a-chip engineering and direct surgical anastomosis

Abstract: We report the fabrication of a scaffold (hereafter referred to as AngioChip) that supports the assembly of parenchymal cells on a mechanically tunable matrix surrounding a perfusable, branched, three-dimensional microchannel network coated with endothelial cells. The design of AngioChip decouples the material choices for the engineered vessel network and for cell seeding in the parenchyma, enabling extensive remodelling while maintaining an open-vessel lumen. The incorporation of nanopores and micro-holes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
509
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 524 publications
(513 citation statements)
references
References 64 publications
(74 reference statements)
2
509
0
2
Order By: Relevance
“…On the other hand, dried-and-crosslinked collagen tubes yielded average burst pressures of *1300 mm Hg, which is comparable to the value obtained by Chaikof and coworkers for tubes of 1.3 mm inner diameter. 18 While this value is still shy of the burst pressure of native arteries (which can be as high as 3000 mm Hg) 25 , it is close to the value for native vein (*1200 mm Hg) 26 and more than sufficient to withstand pressure of arterial flow. Compliance of dried-andcrosslinked tubes averaged *1.7%/100 mm Hg, which is comparable to the value (0.7-2.6%/100 mm Hg) of mammalian vein.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…On the other hand, dried-and-crosslinked collagen tubes yielded average burst pressures of *1300 mm Hg, which is comparable to the value obtained by Chaikof and coworkers for tubes of 1.3 mm inner diameter. 18 While this value is still shy of the burst pressure of native arteries (which can be as high as 3000 mm Hg) 25 , it is close to the value for native vein (*1200 mm Hg) 26 and more than sufficient to withstand pressure of arterial flow. Compliance of dried-andcrosslinked tubes averaged *1.7%/100 mm Hg, which is comparable to the value (0.7-2.6%/100 mm Hg) of mammalian vein.…”
Section: Discussionmentioning
confidence: 68%
“…To the best of our knowledge, nearly all other studies that claim anastomosis between an engineered collagen-based scaffold and native vessels £1 mm outer diameter used a polymer mesh to reinforce the anastomosis, 29 or surgical glue in place of suture. 26 Only a few groups have engineered implantable vascular grafts at the £1 mm scale. Narita and coworkers reported making grafts of 0.7 mm inner diameter from poly-ecaprolactone.…”
Section: Discussionmentioning
confidence: 99%
“…For example, because cardiac cells and blood vessel cells require different culture medium and distinct ECM structure and composition, and mature at different time points, engineering spatially controlled vasculature within a cardiac patch may be a challenge (17,18). To overcome these challenges, recent advances in lithographic methods have enabled the layer-bylayer assembly of anisotropic 3D cardiac tissues and a vascular compartment embedded within them (19)(20)(21). For example, Zhang and colleagues (21) have reported on the production of a biodegradable scaffold with a built-in vasculature.…”
mentioning
confidence: 99%
“…To overcome these challenges, recent advances in lithographic methods have enabled the layer-bylayer assembly of anisotropic 3D cardiac tissues and a vascular compartment embedded within them (19)(20)(21). For example, Zhang and colleagues (21) have reported on the production of a biodegradable scaffold with a built-in vasculature. In a different study Ye and colleagues (20) reported the stacking of elastomeric microvessels and heart cell scaffolds to form 3D vascularized tissues.…”
mentioning
confidence: 99%
“…Also, by integrating vasculature models into the ECTs, such as the recent AngioChip (Figure 1(j-m)) [20], a circulatory system could be generated to investigate drug delivery methods as well as the effect of the endothelium. Finally, since most drug delivery methods can result in a systemic exposure to either the drug or its by-products, micro tissues corresponding to the clearance organs, the liver and kidney, upstream of the ECT compartment could provide valuable information about the interaction of the drug with these organs and the downstream consequences.…”
Section: Expert Opinionmentioning
confidence: 99%